Automatic Water System of Greenhouse - Prokop, M. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2015)
The objective of this thesis is a design of automatic water system of greenhouse, which will be able measure temperature, relative humidity of air and soil. System will control air and water management based on these values.
Keywords: temperature measuring; relative humidity measuring; automatic control; water system